Distinct T cell signatures are associated with Staphylococcus aureus skin infection in pediatric atopic dermatitis - Clowry, Julianne; Dempsey, Daniel J.; Claxton, Tracey J.; Towell, Aisling M.; Turley, Mary B.; Sutton, Martin; Geoghegan, Joan A.; Kezic, Sanja; Jakasa, Ivone; White, Arthur; Irvine, Alan D.; McLoughlin, Rachel M. (JCI insight, 2024)
Atopic dermatitis (AD) is an inflammatory skin condition with a childhood prevalence of up to 25%. Microbial dysbiosis is characteristic of AD, with Staphylococcus aureus the most frequent pathogen associated with disease flares and increasingly implicated in disease pathogenesis. Therapeutics to mitigate the effects of S. aureus have had limited efficacy and S. aureus-associated temporal disease flares are synonymous with AD. An alternative approach is an anti-S. aureus vaccine, tailored to AD. Experimental vaccines have highlighted the importance of T cells in conferring protective anti-S. aureus responses; however, correlates of T cell immunity against S. aureus in AD have not been identified. We identify a systemic and cutaneous immunological signature associated with S. aureus skin infection (ADS.aureus) in a pediatric AD cohort, using a combined Bayesian multinomial analysis. ADS.aureus was most highly associated with elevated cutaneous chemokines IP10 and TARC, which preferentially direct Th1 and Th2 cells to skin. Systemic CD4+ and CD8+ T cells, except for Th2 cells, were suppressed in ADS.aureus, particularly circulating Th1, memory IL-10+ T cells, and skin-homing memory Th17 cells. Systemic γδ T cell expansion in ADS.aureus was also observed. This study suggests that augmentation of protective T cell subsets is a potential therapeutic strategy in the management of S. aureus in AD.